Effect of difference between EV-A71 virus epidemic strain and "vaccine strain" on neutralizing antibody titer - Yiwei Ding; Zhihai Han (Taylor & Francis Group, 2022)
Hand, foot and mouth disease was mainly caused by EV-A71 virus. The main antigen structure of VP1 region of EV-A71 was easily varied. Here, we investigated the seroprevalence of EV-A71 based on a large group of healthy individuals in Beijing, China, in order to study the effectiveness of EV-A71 vaccine in a real-world setting. BrCr and the clinical strain isolated from the Chinese mainland in 2008 ("vaccine strain:"CMU4232/BJ/CHN/2008), EV-A71 C4 epidemic strains isolated in 2010, 2013, and 2016, were tested for neutralizing antibodies (NtAb) in every year. Phylogenetic tree analysis of the EV-A71 strains above, as well as amino acid composition homologous sequence analysis were applied. The "vaccine strain" has 83.0% homology with FY23, H07 and FY7VP5. It belongs to the same branch of C4a as 10 C4, 13 C4 and 16 C4, and differs from the amino acid sites 283 and 293 of 16 C4. Compared with "vaccine strains," there was a significant difference between the 50-59 years old age group when the NtAb titer of 16 C4 strain was 1:512-1:1024. Our results suggest that changes in the functional epitopes of NtAb caused by amino acid 283 and 293 loci in EV-A71 strains may affect the production of neutralizing antibodies.